Think Tank—Back to the Future: A NanoGold Standard Proposal. Issue 5 (July 2015) - Faugère, Christophe
<x xml:space="preserve">Abstract</x> Gold and other precious metals have acted as a medium for economic exchange for millennia, and currencies based on gold have always had a certain attraction. Because gold is an exhaustible, nonrenewable resource, however, many economists view the gold standard, where the prices of currencies are fixed in terms of a specified amount of gold, as a recipe for economic depression in the long term. An exploration of a proposal to return to a gold standard based on NanoGold examines the practical implications of backing paper currency with minute quantities of gold. Advances in digital technology make it possible for NanoGold particles to serve as a viable medium of exchange—provided people can measure it accurately, validate its tangibility in transactions, and accept it as a new social norm. The undesirable effects of the private holding of gold flooding the economy can be avoided if central banks can enforce a minting monopoly on NanoGold particles. If these conditions are met, it might be possible that paper money will have a true backing and monetary policy can generate price stability and postpone deflation to an infinitely distant future. ©2015 Wiley Periodicals, Inc.